Facing the surgeon's nightmare: Incidence and management of postoperative pancreatic fistulas grade C after pancreaticoduodenectomy based on the updated definition of the International Study Group of Pancreatic Surgery (ISGPS). (14th February 2020) - Luu, Andreas Minh; Krasemann, Lukas; Fahlbusch, Tim; Belyaev, Orlin; Janot‐Matuschek, Monika; Uhl, Waldemar; Braumann, Chris
Abstract: Background: Postoperative pancreatic fistulas (POPF) grade C represent a rare but feared complication following pancreaticoduodenectomy (PD). They can contribute significantly to postoperative morbidity and mortality. Methods: We performed a retrospective chart review for all patients who had undergone pancreatic head resection between 2007 and 2016 to identify those who suffered from POPF grade C according to the updated definition of the International Study Group of Pancreatic Surgery (ISGPS). Results: A total of 722 patients underwent PD. Twenty‐three patients (3.19%) developed a POPF grade C. Cardiovascular diseases, soft pancreatic texture and main pancreatic duct diameter were identified as risk factors ( P < .05). Reoperation was necessary in all affected patients on postoperative day 12 ± 9 on average. Mortality was significantly associated with POPF grade C ( P < .05) being present in 39.1% (9/23). Conclusions: POPF grade C after PD remains a serious complication with a high level of morbidity and mortality. Surgical treatment is the sole curative therapy and thus the treatment of choice. Abstract : Highlight Postoperative pancreatic fistulas grade C are a rare complication contributing significantly to postoperative morbidity and mortality. Completion pancreatectomy is the sole curative therapy which must be initiated as quickly as possible.